T3P-promoted synthesis of a series of novel 2-aryl-3-phenyl-2, 3, 5, 6-tetrahydro-4H-1, 3-thiazin-4-ones. Issue 18 (30th April 2020) - Silverberg, Lee J.; Pacheco, Carlos; Sahu, Debashish; Mal, Tapas; Scholl, Peter; Sobhi, Hany F.; Bradley, Heather G.; Cardenas, Omar A.; Gonzalez, Kyanna M.; Islam, Jasra M.; Kimmel, Emily G.; Li, Winnie; et al.
Graphical abstract: Highlights: T3P/pyridine promoted the reaction of imines with 3-mercaptopropionic acid. 2-Aryl-3-phenyl-2, 3, 5, 6-tetrahydro-4 H -1, 3-thiazin-4-ones were readily prepared. Both electron-withdrawing and -donating groups worked on the 2-aryl ring. The reaction can be done as a 2-component reaction or as a 3-component reaction. Abstract: A series of twelve novel 2-aryl-3-phenyl-2, 3, 5, 6-tetrahydro-4 H -1, 3-thiazin-4-ones was prepared at room temperature by T3P-mediated cyclization of C -aryl- N -phenyl imines with 3-mercaptopropionic acid. The reaction can also be run as a 3-component reaction, forming the imine in situ . The reactions were operationally simple, rapid and gave yields as high as 75%. This provides ready access to C -aryl- N -phenyl compounds in this family, which have been generally difficult to prepare.